INCOMPATIBILITY OR CONVERGENCE: HUMAN LIFE AS CAPITAL - N. M. Boichenko; Z. V. Shevchenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2020)
The purpose of the study is to identify a common theoretical basis for the study of human life as capital and unconditional higher value. Theoretical basis is based on the value-laden and revised structural constructivism, provided by the French philosopher and sociologist Pierre Bourdieu, critical analysis of the concepts of capital as the embodiment of social expectations, the biological concept of the value of human life, as well as the concepts of its sanctity. Originality. It is proved that one should not consider the value of human life as capital only but instead takes into account its different value interpretations, especially when forming the social identity of a person. Moreover, in each of the value systems, the value of human life can be recognized as unconditional, which does not prevent the coexistence of such different value interpretations within the framework of one social identity, which then inevitably becomes a multiple social identity. Conclusions. Human life cannot be considered as a result of integrating economic expectations into the concept of "advertising" capital: first, expectations may well be inadequate; second, expectations by themselves are not directly related to capital; third, expectations do not necessarily lead to development; fourth, one should clearly distinguish between the spontaneous "expectations" and the values that express people’s strong motivation as members of social communities. The multiplicity of possible cultural conditions that affirm the unconditional value of life indicates that this unconditionality is always relevant rather than absolute. The multiple social identities could be used to add value to the protection of human life, the affirmation of multiple social identities is a means of affirming the unconditional value of human life – it is unconditional in several alternative ways.